2021
DOI: 10.1111/jocn.15931
|View full text |Cite|
|
Sign up to set email alerts
|

The relation between psychological distress and medication adherence in lung transplant candidates and recipients: A cross‐sectional study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Finally, the components of personality and adherence to treatment, except for responsibility, are predictors of stress, among which the predictive flexibility is stronger ( Allahmoradi et al, 2022 ). In another study, Wessels-Bakker et al, (2022) found that symptoms of anxiety and medication adherence were significantly and positively related in transplant recipients. They found no association between depressive or post-traumatic stress symptoms, and medication adherence ( Wessels-Bakker et al, 2022 ).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Finally, the components of personality and adherence to treatment, except for responsibility, are predictors of stress, among which the predictive flexibility is stronger ( Allahmoradi et al, 2022 ). In another study, Wessels-Bakker et al, (2022) found that symptoms of anxiety and medication adherence were significantly and positively related in transplant recipients. They found no association between depressive or post-traumatic stress symptoms, and medication adherence ( Wessels-Bakker et al, 2022 ).…”
Section: Discussionmentioning
confidence: 96%
“…In another study, Wessels-Bakker et al, (2022) found that symptoms of anxiety and medication adherence were significantly and positively related in transplant recipients. They found no association between depressive or post-traumatic stress symptoms, and medication adherence ( Wessels-Bakker et al, 2022 ). Omranifard et al (2017) showed that there was no significant relationship between anxiety and compliance of kidney transplant patients.…”
Section: Discussionmentioning
confidence: 96%
“…Anxiety refers to an individual’s subjective negative emotional state (Zung, 1971). About 33.7% of lung transplant patients experience postoperative anxiety, which is a common psychological problem in lung transplant patients (Wessels-Bakker et al, 2022). Some studies have suggested that anxiety may be related to patients’ unmet care needs (Kabak et al, 2021; Molassiotis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Wessels‐Bakker et al (2022), the first column in Table 3 should be replaced with revised wording. The data are not affected.…”
Section: Candidates (N = 73) N (%) Recipients (N = 116) N (%)mentioning
confidence: 99%